1987
DOI: 10.1677/joe.0.1130045
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of dopamine and noradrenaline in the regulation of prolactin secretion from an ectopic anterior pituitary gland in female rats

Abstract: It was recently reported that anterior pituitary tissue transplanted to an ectopic site contains measurable amounts of dopamine and noradrenaline. To examine the possibility of local catecholaminergic control of prolactin secretion from ectopic pituitaries, pituitary grafted and sham-operated female rats were submitted to several pharmacological treatments modifying catecholamine synthesis. Administration of a single dose of alpha-methyl-p-tyrosine (alpha-MPT) significantly reduced dopamine content in the graf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…As expected, pituitary grafting increased hypothalamic DA turnover, as measured by the DOPAC/DA index, confirming previous studies (Cramer et al 1979, Gudelsky & Porter 1979, Esquifino et al 1987a). There was also a decrease in hypothalamic NE and serotonin contents, the latter only at 8 days (King et al 1985).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…As expected, pituitary grafting increased hypothalamic DA turnover, as measured by the DOPAC/DA index, confirming previous studies (Cramer et al 1979, Gudelsky & Porter 1979, Esquifino et al 1987a). There was also a decrease in hypothalamic NE and serotonin contents, the latter only at 8 days (King et al 1985).…”
Section: Discussionsupporting
confidence: 91%
“…Differential PRL regu¬ latory mechanisms operating on the ectopie tissue have also been observed (Fernández-Ruiz et al 1987a, Agrasal et al 1988, 1989, and confirmed by finding high levels of DA and its biosynthetic enzyme, tyrosine hydroxylase, in the ectopie gland (Iturriza et al 1983. Furthermore the ectopie pituitary gland can release hormones other than PRL (Esquifino et al 1987a). …”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations